![image](https://tex.z-dn.net/?f=x%5E2%28-x%5E2-49%29+%5Cgeq+49%28-x%5E2-49%29%5C%5C%5C%5Cx%5E2%28-x%5E2-49%29-49%28-x%5E2-49%29%5Cleq+0%5C%5C%5C%5C%28-x%5E2-49%29%28x%5E2-49%29+%5Cleq+0%5C%5C%5C%5C-%28x%5E2%2B49%29%28x%5E2-49%29+%5Cleq+0%5C%5C%5C%5C%28x%5E2%2B49%29%28x-7%29%28x%2B7%29++%5Cgeq+0%5C%5C%5C%5C%28x%5E2%2B49%3E0%2Cx%5Cin+R%5C%5C%5C%5C%28x-7%29%28x%2B7%29+%5Cgeq+0%5C%5C%5C%5C%2B+%2B+%2B+%2B+%2B%28-7%29-+-+-+-+%287%29%2B+%2B+%2B+%2B+%2B+%5C%5C%5C%5Cx%5Cin%28-%5Cinfty%2C-7%29U%287%2C%2B%5Cinfty%29)
0,x\in R\\\\(x-7)(x+7) \geq 0\\\\+ + + + +(-7)- - - - (7)+ + + + + \\\\x\in(-\infty,-7)U(7,+\infty)" alt="x^2(-x^2-49) \geq 49(-x^2-49)\\\\x^2(-x^2-49)-49(-x^2-49)\leq 0\\\\(-x^2-49)(x^2-49) \leq 0\\\\-(x^2+49)(x^2-49) \leq 0\\\\(x^2+49)(x-7)(x+7) \geq 0\\\\(x^2+49>0,x\in R\\\\(x-7)(x+7) \geq 0\\\\+ + + + +(-7)- - - - (7)+ + + + + \\\\x\in(-\infty,-7)U(7,+\infty)" align="absmiddle" class="latex-formula">